Rupturing the laws of discourse: Learner agency in the construction of their identity in school discourses - Saloshna Vandeyar; Lwazi Ziqubu (Perspectives in Education, 2022)
Utilising the theoretical frameworks of theory of power and theory of performativity, this case study explored how learners exercised agency in the construction of their identity in school discourses. Data capture incorporated a mix of a survey, semi-structured interviews and field notes. Data was analysed using content analysis. A total of 90 learners participated in the survey. Fifteen learners, three teachers and three principals participated in semistructured interviews. This paper reports on findings from the semistructured interviews. Findings were twofold. First, schools used Foucault’s mechanisms and instruments of constructing learner identity. Learners were subjected to a constant gaze at schools. Second, learners became agentic in schools and asserted their own identities. Some of these identities clashed with the identity of the ‘ideal learner’ of schools. Despite established subject positions in schools, learners created their own subject positions to counter limiting and constraining identities that were imposed by the school.